Which Structural Reforms Does E(M)U Need to Function Properly? - Kurt Bayer (The Vienna Institute for International Economic Studies (wiiw), 2018)
Structural reform proposals have undergone significant change both as proposed by IMF and OECD as by the European Union. From a narrow flexibility-enhancing ('liberalising') focus complementing a strict budget consolidation course, they have evolved towards embracing institutional reforms and promoting of growth and productivity. Some of these reform proposals are motivated by increasing divergence between Member States since the financial crisis, others attempt to compensate for the fact that EMU did not and does not yet constitute an optimal currency area with all its institutions required. This paper analyses the various motivations and restrictions for structural reforms and proposes an even wider array of additional reforms, with the aim to enhance socio-economic-environmental sustainability and well-being in the European Union ('progressive' reforms). 'Progressive reforms' should establish equivalence between economic, social and environmental objectives. Excessive 'financialisation' of the economy should be reversed by promoting longer-term real investment decisions, by slowing financial trading decisions, by increasing capital requirements of financial institutions, by levying financial transactions taxes, etc. Productivity-oriented wage setting and working conditions procedures through collective bargaining covering a wide spectrum of the labour force should be promoted as enhancing workers' well-being and be balanced with flexibility requirements. Industrial policies aimed at enhancing the innovative capabilities of countries, with appropriate education, patent and innovation interventions need to gain wide-spread acceptance. The 'race to the bottom' with respect to corporate and personal income taxation, as well as generous tax-reducing policies need to be prevented. National and regional preferences with respect to social and cultural aspects need to be exempted from competition rules, as manifestations of social cohesion, environmental protection and identity-preserving heritage. In cases where cross-country spillovers matter, such 'progressive' structural policies should be set as general framework conditions by the European Union but be adjusted and implemented by the Member States.
Keywords: E24; F45; O43; 330; structural reform; economic growth; institutional reform; Economic and Monetary Union; European Union